2013
DOI: 10.1007/s10549-013-2782-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences regarding intraoperative versus external beam radiotherapy following breast-conserving surgery

Abstract: The TARGIT-A Trial is an international randomized, prospective trial comparing intraoperative radiotherapy (IORT) for equivalence to external beam radiotherapy (EBRT) following lumpectomy for invasive breast cancer in selected low-risk patients; early results suggest that outcomes are similar. In addition to effectiveness data and cost considerations, the preferences of patients should help inform practice. This study was undertaken to explore and quantify preference in choosing between IORT and the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 20 publications
1
33
0
4
Order By: Relevance
“…101,103,104 It is much smaller than the 7.5% margin in the ELIOT trial 105 and lower than the difference considered 'acceptable' by the CALGB (5% difference) 11 and Post-operative Radiotherapy In Minimum-risk Elderly (PRIME) II (3% difference) 106 studies. At this boundary, TARGIT was non-inferior to EBRT (P non-inferiority < 0.00001).…”
Section: Non-inferiority For Local Recurrencementioning
confidence: 89%
See 2 more Smart Citations
“…101,103,104 It is much smaller than the 7.5% margin in the ELIOT trial 105 and lower than the difference considered 'acceptable' by the CALGB (5% difference) 11 and Post-operative Radiotherapy In Minimum-risk Elderly (PRIME) II (3% difference) 106 studies. At this boundary, TARGIT was non-inferior to EBRT (P non-inferiority < 0.00001).…”
Section: Non-inferiority For Local Recurrencementioning
confidence: 89%
“…The pre-specified non-inferiority boundary of a 2.5% absolute difference in local recurrence is very conservative and has been validated in patient preference studies. 101,103,104 At this boundary, TARGIT is non-inferior to EBRT (P non-inferiority < 0.00001) ( Figure 38). Furthermore, we have recommended that TARGIT should be used during the initial lumpectomy, as in the prepathology stratum (note that this is a stratum not a subgroup), when the difference between the two treatments was undoubtedly not statistically significant (p = 0.31).…”
Section: Further Analysis As Requested By the National Institute For mentioning
confidence: 98%
See 1 more Smart Citation
“…64 However, it should be noted that, when the non-inferiority margin was chosen, the estimated local recurrence rate (LRR) (based on the literature available in 1999) 70,71 was 6%, and since then recurrence rates have fallen. Two patient preference studies 72,73 suggest that patients would be willing to accept an increase in the risk of local recurrence for the convenience of INTRABEAM treatment but it should be noted that these studies were conducted in countries in which WB-EBRT is typically delivered over 5-6 weeks and it is not known whether or not patient preference would be similar in England where WB-EBRT is typically delivered over 3 weeks.…”
Section: Designmentioning
confidence: 99%
“…A quality-oflife study of 87 women included on the TARGIT study demonstrated less pain and improved functioning in patients receiving IORT over WBI [64]. In a survey of patients previously treated with BCT, Alvarado et al demonstrated that 91% of patients surveyed would prefer IORT if IBTR was noninferior and 64% would accept a median 2.3% higher risk for IBTR if it meant simplifying RT with IORT [65]. Therefore, considerations of comparative effectiveness and cost-effectiveness of IORT relative to other adjuvant RT options should encompass the aforementioned additional potential benefits of IORT that are generally not evaluated in clinical trials.…”
Section: • • Cost-effectivenessmentioning
confidence: 99%